Tension and Resolution: Dynamic, Evolving Populations of Organelle Genomes within Plant Cells - Johnston, Iain G. (Molecular plant, 2019)
Mitochondria and plastids form dynamic, evolving populations physically embedded in the fluctuating environment of the plant cell. Their evolutionary heritage has shaped how the cell controls the genetic structure and the physical behavior of its organelle populations. While the specific genes involved in these processes are gradually being revealed, the governing principles underlying this controlled behavior remain poorly understood. As the genetic and physical dynamics of these organelles are central to bioenergetic performance and plant physiology, this challenges both fundamental biology and strategies to engineer better-performing plants. This article reviews current knowledge of the physical and genetic behavior of mitochondria and chloroplasts in plant cells. An overarching hypothesis is proposed whereby organelles face a tension between genetic robustness and individual control and responsiveness, and different species resolve this tension in different ways. As plants are immobile and thus subject to fluctuating environments, their organelles are proposed to favor individual responsiveness, sacrificing genetic robustness. Several notable features of plant organelles, including large genomes, mtDNA recombination, fragmented organelles, and plastid/mitochondrial differences may potentially be explained by this hypothesis. Finally, the ways that quantitative and systems biology can help shed light on the plethora of open questions in this field are highlighted. Complex life is powered by mitochondria and plastids, which form dynamic, evolving populations within plant cells. Here, we review the coupled physical and genetic behavior of these vital populations and hypothesize that an evolutionary tension can account for several dramatic differences between plant organelles and those in other kingdoms.